Impact of Urinary Bladder Filling on Prostate Volume Prediction using Fractal Dimension Analysis of Ultrasound Images: A Cross-sectional Study - Sakshi Jaiswal; Prabhu Kaliyaperumal; Vijayalakshmi Nagarajan; A Kumaravel; Balasubramanian Shanthi; Murugan Gopalakrishnan; M Vijayamalathi (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Fractal Dimension (FD) analysis has emerged as a powerful tool for quantifying the morphological complexity of structures in medical images, including the analysis of cancerous tissue. Because the prostate is located inferior to the neck of the urinary bladder, accurate measurement is essential for the reliable diagnosis and treatment of clinical conditions such as Benign Prostatic Hyperplasia (BPH) and prostate cancer. Aim: To evaluate whether urinary bladder filling status affects prostate FD and the accuracy of FD-based volume prediction models. Materials and Methods: A cross-sectional study using a matched-pairs (within-subject) design was conducted at the Department of Radiology, Chalmeda Anand Rao Institute of Medical Sciences, Telangana, India, from September 2025 to December 2025. The study was carried out on 42 male ultrasonographic images of the prostate gland acquired with a filled and an empty urinary bladder (filled = 21, empty = 21). Prostate FD and volume prediction accuracy were measured using fractal analysis software and compared between the two bladder states using a paired t-test. Results: The study population had a mean age of 52.58±5.43 years. The RMSE for volume prediction was 0.4071 mL (filled bladder) and 0.4106 mL (empty bladder). The mean FD value of the prostate gland was 1.52 in both filled and empty bladder conditions. No statistically significant association was observed between bladder filling status and prostate volume prediction accuracy or FD. Conclusion: The findings of the present study indicated that urinary bladder filling status had minimal impact on prostate morphology.